ANALISIS PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS, LEVERAGE, DAN SIZE TERHADAP NILAI PERUSAHAAN - Abdul Basir (LP2M Universitas Bina Bangsa, 2024)
This study aimed to examine the influence of dividend policy, profitability, leverage, and size on firm value. This research was a quantitative study. The type of data was secondary data obtained from www.idx.co.id and company website. The populations of research were banking companies which is listed in Indonesia Stock Exchange during 2014-2016 period. While the samples of this study determined by purposive sampling method. The total of data were 111. The analysis method was multiple linear regression analysis. The result of this study indicated that dividend policy and size had no influenced the firm value, while profitability and leverage influenced the firm value